Failure analysis of metallic materials in sheet metal forming using finite element method - Pedro teixeira (2008)
The optimisation of sheet metal processes by using numerical simulations has become a key factor to a continuously increasing requirement for time and cost efficiency, for quality improvement and materials saving, in many manufacturing areas such as automotive, aerospace, building, packaging and electronic industries. The introduction of new materials brought new challenges to sheet metal forming processes. The behaviour observed with conventional steels may not be applied when using high-strength steels or aluminium alloys. Numerical codes need to model correctly the material and different constitutive equations must be considered to describe with greater accuracy its behaviour. This enhancement of material description may provide a better prediction of the forming limits, enabling an assessment of the influence of each forming parameter on the necking occurrence and the improvement of press performance. This paper presents two numerical approaches for failure prediction in sheet metal forming operations: one is the implementation of the Lemaitre's ductile damage model in the Abaqus/Explicit code in accordance with the theory of Continuum Damage Mechanics and the other is the traditional use of FLDs, usually employed as an analysis of the finite element solution in which the necking phenomenon is carried out in the framework of Marciniak-Kuczinsky (M-K) analysis coupled with the conventional theory of plasticity. The previous strategies and corresponding results are compared with two experimental failure cases, in order to test and validate each of these strategies.